Avaliação do fibrinogênio, tempo de protrombina tempo de tromboplastina parcial ativada e fatores de risco em pacientes com infarto agudo do miocárdio - Dias, Marinês Lavall (2006)
It was looked to stand out the importance of discover laboratorial parameters that are auxiliary to the diagnostic of acute infarction of myocardial (AMI). The AMI is one of the biggest problems of public health in the world. Due to this fact, it is of major importance to find laboratorial parameters with quality and reasonable costs. In the present study fibrinogen concentrations measured during acute phase of AMI were related to cardiovascular death or a new AMI event. This incidence was higher in the etary range of 44 to 75 years in men; and 56 to 90 in women. Approximately 73% of patients presented familiar history of Coronary Heart Disease (CHD), 66% smoked, 63% presented hypertension and 81% sedentary. It was also observed elevated cases of AMI in extreme temperature days. For the fibrinogen concentrations (FBR), results demonstrated significant difference (p<0.05) between the control and infarction group patients. For protrombin time, troponine (TROP), creatinokinase, CK-MB and leukocytes count, results showed statically difference between groups. However, TTPa, total cholesterol, HDL, LDL, triglycerides levels presented no significant difference between studied groups. In conclusion, this work demonstrated a increasing fibrinogen concentration in patients with AMI, revealing that it may be adequate as a cardiac marker for AMI.